Faktor Faktor Yang Berhubungan Dengan Penggunaan Metode Kontrasepsi Jangka Panjang Di Puskesmas Pangkalan Balai Kabupaten Banyuasin Tahun 2023 - Hesi Yusdana; Dainita Ekawati; Syntia Rahutami; Dewi Suryanti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
The contraceptive method is the long-term use of contraception to delay, prevent or space out pregnancy. Factors related to the use of long-term contraceptive methods at the Pangkalan Balai Health Center, Banyuasin Regency in 2023. The design of this study was a quantitative analytic survey with a cross sectional approach. The population in this study is the number of couples of childbearing age (PUS) in 2022, totaling 10290 respondents. Sampling using slovin theory. The sample in this study amounted to 99 people. How to take samples using purposive sampling. This research was carried out from 27 May 2023 to 24 June 2023. Data collection used a questionnaire. Bivariate data analysis using the Chi-Square test. The results showed that there was a relationship between knowledge (p value 0.000), availability of contraceptives (p value 0.001), and the role of staff (p value 0.008) with the use of long-term contraceptive methods at the Pangkalan Balai Health Center, Banyuasin Regency in 2023. . There is no relationship between education (p value 0.542), husband's support (p value 0.46) and parity (p value 0.274) with the use of long-term contraceptive methods at the Pangkalan Balai Health Center in Banyuasin Regency in 2023. Strengthen family planning program activities, and provide education to community so that the target achievement can be implemented properly.